Determining factors on level of knowledge regarding pap smear among married women in Hulu Langat district, Selangor - M Jamsiah (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Cervical cancer can be prevented through pap smear screening and its proper management of high risk cases. High level of knowledge regarding pap smear screening will encourage women to do pap smear as recommended. Methadology : A cross sectional study was carried out in Jun 2007 to find out the level of knowledge regarding pap smear among married women in Kg. Sesapa Kelubi, Hulu Langat Selangor. Universal sampling was conducted using guided questionnaire and data was analysed using SPSS version 12. Result : A total of 154 women participated in this study. Only 3.9% of respondents practiced pap smear as recommended and only 51.3% of them have high level of knowledge with 27.9% has no knowledge regarding pap smear. Women between the ages of 20-35 years old have higher level of knowledge (77.9%). The only factor that showed significant association with level of knowledge in this study is level of education. Age, income, gravida and occupation did not show any significant association. Conclusion : The effectiveness of pap smear screening program should be regularly evaluated to determine the problem of its low coverage. Proper strategy should be planned to increase knowledge among women and their participation in pap smear program.